The eradication of pea weevil Bruchus pisorum (L.) (Coleoptera: Chrysomelidae) from New Zealand - David G. Voice; Rory MacLellan; Adrian Russell; Dave Goulden; Ivan Lawrie; Greg Baker; David A. J. Teulon; John M. Kean (CABI Agriculture and Bioscience)
Abstract Pea weevil (Bruchus pisorum (L.), Coleoptera, Chrysomelidae) is a major cosmopolitan pest of pea crops and is established in most pea growing areas of the world. Pea weevil has been detected several times in New Zealand, but these incidents never resulted in an established population. Establishment occurred in 2016, when pea weevil was detected in stored and field peas in the Wairarapa region of the North Island. After due consideration, including initial delimiting surveys and analysis of potential pathways, the Ministry for Primary Industries (MPI), in consultation with industry and community interests, decided to attempt eradication. The eradication programme utilised a range of tactics including a regionalised pea growing ban, movement restrictions for pea plant material, pea trap crops managed with insecticides and herbicides, and physical pea plant destruction to prevent regrowth. Trap crops played a dual role for local surveillance and beetle destruction. A national survey for pea weevil was also undertaken. The eradication programme was implemented under national New Zealand legislation (including a Controlled Area Notice) and an awareness raising media campaign. The initial pea weevil infestation was found over an area of approximately 115,000 ha. National surveillance resulted in no pea weevil detections outside of the Wairarapa Controlled Area. In the first year of the eradication programme (spring 2016–2017), the pea weevil population was reduced by 99.1%. Zero detections of pea weevil were found in the spring of 2018 and 2019, confirming eradication, and the planting ban and movement restrictions were lifted in 2020. This paper details what appears to be the first documented eradication of pea weevil anywhere in the world and explores the technical challenges, options, and tactics which eventually led to this successful eradication.